A study of the effects of maternal high fat diet on behavioural responses to acute and repeated administrations of cocaine in rat offspring. (23rd April 2018) - Sasaki, Aya; McGowan, Patrick O.; Erb, Suzanne
Highlights: Both male and female adult offspring were responsive to the acute activational effects of cocaine. Both male and female adult offspring exhibited a strong cocaine-conditioned locomotor response after repeated cocaine. Maternal diet did not interact in these effects of cocaine. Maternal high fat diet (HFD) enhanced the expression of behavioural anxiety in female adult offspring. Cocaine reversed the effect of maternal HFD on the expression of behavioural anxiety in female offspring. Abstract: Building on previous work in the field, we examined the effect of maternal high fat diet (HFD) during gestation and lactation on the sensitivity of male and female adult offspring to acute and repeated cocaine exposures, and to the expression of cocaine-induced anxiety in the elevated plus maze (EPM). In both male and female offspring, acute injections of cocaine induced a strong locomotor-activating effect; repeated injections produced a robust conditioned locomotor response to the context in which they were given cocaine, and heightened activity in response to a subsequent acute challenge of cocaine. Although female offspring of HFD relative to control house chow diet (CHD) dams exhibited a generally elevated level of locomotor activity, this effect was not further enhanced by cocaine administration/s and there were no significant interactions between maternal diet and cocaine in either male or female offspring. Finally, female offspring of HFD relative to CHD dams exhibited enhanced behavioral anxiety in the EPM, an effect that was reversed when the offspring were exposed to cocaine 48 h prior. Although, in contradiction to our hypotheses, the present study failed to demonstrate an effect of maternal diet on the locomotor-activating effects of cocaine, it did replicate all of the established findings upon which its rationale and predictions were based. Thus, we believe that our results provide important context for future studies.